Simulation of Trucks Haulage Operation at Ashaka Cement Company in Gombe State, North-Eastern Nigeria - Luqman K. SALATI; Sani D. MUHAMMAD; Jacob T. ADEYEMO (FUDMA Journal of Engineering and Technology, 2026)
This study examined the simulation of truck haulage operation at Ashaka Cement Company in Ashaka, Gombe State, North-eastern Nigeria. Data collected included cycle time, tonnage of limestone produced and truck capacity. Field data plotted on Microsoft Excel software was used in generating prediction equations through polynomial model expressions. The model was then validated using historical data of truck haulage, and subsequently simulated. Results of the study showed that the optimum cycle time of North-North pit was 39 minutes long, producing 7587 tonnes per day, the cycle time for the North-West pit was 26 minutes, peaking 8100 tonnes per day; and the South-West pit cycle time, lasted 19 minutes and reaching up to 8640 tonnes per day respectively. The findings imply that truck haulage operation in the company has attained optimum production. To sustain this feat, it was recommended that hindrances to production such as boulders hook (over size), buildup of wet material and cleaning-associated delays (rollers, affront feeder) should be minimised to the bearest minimum.